Vers une théorisation du discours séducteur - Sandrine SORLIN (E-REA)
Seduction occupies a fundamental place in the history of human relations, as it seems to have initiated ‘softer’ kinds of interaction with the other, sometimes superseding physical violence. This introduction attempts a theorisation of seductive discourse that goes beyond amorous relations to include the art of seduction in politics, advertising, literature or ideology. It intends to bring to the fore the linguistic, stylistic, cognitive and pragmatic springs of these strategies of influence which seem to be inherent to everyday speech. In its most extreme version, the aim of seductive discourse is to lead the reader/listener astray, ‘away from her self’, towards the vision or opinion held by the writer/orator. The article displays to what extent the art of seduction can be said to retain part of the violence that it was meant to replace. This E-rea issue is the result of the work carried out within a seminar series on “seductive discourse” organised at Aix-Marseille University. The different articles that compose it reveal the linguistic masks and the discursive strategies of seduction in various corpora and from different perspectives.